Carrera, J. (2011). Algo más que mercachifles. Pulperos y pulperías en la campaña bonaerense, 1770-1820. Rosario: Prohistoria, 236 p. - Rodríguez, Benjamín Matías (2013)
Fil: Rodríguez, Benjamín Matías. Universidad Nacional de Mar del Plata.